Ensuring dynamic stability of constant power loads in future dc distribution power systems using active damping - Pizniur, O.; Shan, Z.; Jatskevich, J. (Енергетика і автоматика, 2015)
DC distribution is widely used in telecom and data centres, and it is envisioned to get wide acceptance in microgrid and buildings’ power systems in the near future as a viable alternative to conventional AC systems. The main building blocks of DC power systems are switching power converters and rectifiers that have nonlinear characteristics. When the voltages are tightly regulated, the converters will act as constant power loads (CPLs). The CPL is known to exhibit the negative incremental impedance and may cause the dynamic instability of the system. The problem associated with CPLs is traditionally tackled using passive damping which has serious drawbacks such as increased size, decreased reliability and efficiency of the system. This paper introduces an active method to inject damping current into the power bus employing an auxiliary power circuit. The proposed approach ensures that the system operates with sufficient stability margin in a small-signal sense. Comparing with previous works, the advantage of the proposed damping circuit is that the absorbed energy for damping is transferred into a neighbouring bus with minimal energy losses.